Australian spore-feeding thrips of the genus Phaulothrips (Thysanoptera, Idolothripinae) - Mound, Laurence A.; Tree, Desley J. (Zootaxa, 2013)
Breeding by several of the spore-feeding species in the genus Phaulothrips is shown to be associated with abandoned tunnels of bees and scolytid beetles, as well as with the dead seed capsules of Eucalyptus species. The breeding sites for other species in the genus remain unknown, but 16 species are here recognised from Australia, of which the following six are newly described: P. daguilaris, P. flindersi, P. kingae, P. kranzae, P. oakeyi, P. whyallae.